The American presidents, Washington to Tyler: what they did, what they said, what was said about them, with full source notes - Nowlan, Robert A. (McFarland & Co., 2012)
"Through current day, only forty-three men have held the office of the President of the United States, and some have been sanctified and some reviled. This historical work addresses the careers of the first ten presidents, men who made vital contributions not only to the office of the presidency, but to the course of the fledgling nation"–Provided by publisher.
Keywords: 1789-1815; United States; 1815-1861; Biography; United States; Politics and government; Presidents; United States; dept.mat; faculty_collection